"We call it put him away": Contemporary Delaware burial practices and NAGPRA. (April 2016) - Obermeyer, Brice
An ethnographic approach for documenting the funerary nature of museum objects is offered to complement existing practices for documenting collections under Native American Graves Protection and Repatriation Act. This approach draws on the Delaware Tribe's work to identify funerary objects affiliated with the Delaware, which indicated that a cemetery, and not simply the graves within it, met the Native American Graves Protection and Repatriation Act definition for a burial site. This approach also revealed that a funerary object would be all the items that were found in association with human remains and/or were recovered from the fill and surface of each individual grave. Using such an approach requires ongoing consultation and engagement with potentially affiliated tribes during the documentation process and will likely result in producing alternative perspectives for documenting collections. Although a more time-intensive approach, it is one that holds greater potential for interpreting the mortuary intent of curated objects.